Persistent Hypoglycemia of Unknown Etiology in a Patient Without Diabetes: A Case Report and Review. (April 2013) - White, Bryan P.; Southwood, Robin
Purpose: This case report reviews the presentation, evaluation, and treatment of persistent hypoglycemia in a patient without a history of diabetes. The use of laboratory tests to differentiate between drug-induced and disease-induced hypoglycemia is reviewed. Summary: A 51-year-old female with multiple medical conditions including bipolar disorder and no history of diabetes was admitted for evaluation and treatment of hypoglycemia. Pharmacotherapy included intravenous dextrose infusions and bolus doses. A battery of tests was ordered to evaluate intrinsic and extrinsic causes. Endocrine Society guidelines for hypoglycemia exist and have recommendations for testing and strategies to rule out drug-related causes. Her insulin level was 57 IU/mL (normal range < 17). Her proinsulin level was 356.8 pmol/L (normal range <8.8). Conclusion: The guidelines recommend a battery of laboratory tests; however, the results are not rapidly available necessitating a structured follow-up process. In our patient, exposure to hypoglycemic agents and exogenous insulin can be ruled out. Autoimmune hypoglycemia or a hypoglycemic reaction to one of her home medications is very unlikely, but cannot be ruled out. An insulinoma is the most likely etiology of her hypoglycemia, but that cannot be confirmed.